Compressive Myelopathy Due to Ossification of the Ligamentum Flavum: Case Report and Review of the Literature - Teles, Alisson R.; Farias, Frederico A. Criscuoli de; Roxo, Marcelo R.; Brasil, Albert Vincent Berthier (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Ossification of the ligamentum flavum (OLF) is a rare condition in which the ligamentum flavum, due to mechanical, biological and genetic factors, becomes ossified. Due to its nature and anatomic location, OLF produces symptoms characteristic of spinal cord compression. The diagnostic confirmation is based primarily on imaging tests such as computed tomography (CT) and magnetic resonance imaging (MRI). Ossification of the ligamentum flavum most often affects Asian populations, rarely occurring in black people. The authors report a case of a 61-year-old black man with progressive paraparesis due to OLF, and review the literature regarding the pathology's prevalence, pathogenesis, clinical features, diagnosis, treatment and prognosis.
Keywords: ossification of the ligamentum flavum; myelopathy; paraparesis; ligamentum flavum; laminectomy; thoracic spine